2017
DOI: 10.3390/s17102434
|View full text |Cite
|
Sign up to set email alerts
|

Precise GNSS Positioning Using Smart Devices

Abstract: The recent access to GNSS (Global Navigation Satellite System) phase observations on smart devices, enabled by Google through its Android operating system, opens the possibility to apply precise positioning techniques using off-the-shelf, mass-market devices. The target of this work is to evaluate whether this is feasible, and which positioning accuracy can be achieved by relative positioning of the smart device with respect to a base station. Positioning of a Google/HTC Nexus 9 tablet was performed by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
71
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 15 publications
1
71
0
4
Order By: Relevance
“…The release of GNSS measurements makes it possible to use proprietary calculation algorithms adapted to the limitations of the equipment and to field conditions of positioning. It also provides an opportunity to analyse the acquired GNSS observations outside the recording device, using external software [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…The release of GNSS measurements makes it possible to use proprietary calculation algorithms adapted to the limitations of the equipment and to field conditions of positioning. It also provides an opportunity to analyse the acquired GNSS observations outside the recording device, using external software [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among these implementations, for instance, Doppler filtering and augmentation were investigated in Reference [4] to reach submeter accuracy. By exploiting carrier-phase observations on the enabled models, it is also possible to smooth code-based pseudorange measurements and reach decimeter-level accuracy without phase-ambiguity resolution, as successfully proposed in Reference [5]. The recent push to achieve precise positioning from Android smartphones thanks to the availability of their raw measurements has also been boosted by the release of a white paper from the European GNSS Agency (GSA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…These varying biases of the code observables are also referred to as group delay variations (GDV).Previous studies by Wanninger and Beer [11] and Wanninger, Sumaya, and Beer [12] have shown that nadir-dependent GDV affect precise point positioning (PPP) based on the single frequency ionosphere-free combination, wide-lane ambiguity fixing based on the Hatch-Melbourne-Wübbena linear combination [13][14][15], as well as TEC estimation of the ionosphere. The latter is an important characteristic of the ionosphere and is necessary in some single frequency precise positioning applications, for instance, precise positioning with mobile devices, which has gained significant attention in recent years [16][17][18][19][20][21][22][23][24][25][26][27]. For the verification and further understanding of these effects, the independent evaluation of previously used methods is therefore important.In this study, we investigated how nadir-dependent GDV affect ionosphere modeling by analyzing the model residuals that they give rise to.…”
mentioning
confidence: 99%